How to save the universe without really trying - Cusick, John (John M.) (Cusick, John (John M.). Dimension why., 2020)
"A 31st-century boy and a 21st-century girl team up to save the universe, evade an evil race of bog mutants, and make a quick pit stop to visit the moon"--Publisher.